Hydatid of Morgagni in Young Female: A Rare Case of Acute Abdomen—Case Report and Literature Review - Taisia Bollettini; Francesco Molinaro; Alice Benigna; Enrico Ciardini; Gabriele Centini; Natale Calomino; Giulia Fusi; Messina Mario; Rossella Angotti (Case Reports in Obstetrics and Gynecology)
Torsion of the hydatid of Morgagni is a rare condition which can cause acute abdominal pain in young female. We present a case report of a 13-year-old girl with acute abdominal pain and treated for torsion of the hydatid of Morgagni. Less than 20 cases of female younger than 18 years old with this condition are been described in the literature. Through our systematic review performed following the PRISMA statement, we want to emphasize the difficulty in diagnosis and the importance of considering this pathology in the differential diagnosis of acute abdomen in females with the aim of obtaining a timely surgical treatment to preserve fertility in these patients.